A Dangerous Engagement #6 Amory Ames - Weaver, Ashley (New York, NY : Minotaur Books, 2019)
"A Dangerous Engagement is the stylish, charming sixth novel in the Edgar-nominated Amory Ames mystery series by Ashley Weaver, set in 1930s New York. As they travel by ship to New York for her childhood friend Tabitha's wedding, Amory Ames gazes out at the city's iconic skyline, excited by the prospect of being a bridesmaid. Her husband Milo, however, is convinced their trip will be deadly dull, since Prohibition is in full swing. But when a member of the wedding party is found murdered on the front steps of the bride's home, the happy plans take a darker twist. Amory discovers that the dead groomsman has links to the notorious-and notoriously handsome-gangster Leon De Lora, and soon she and Milo find themselves drawn into another mystery. While the police seem to think that New York's criminal underworld is at play, Amory feels they can't ignore the wedding party either. Tabitha's fiance Tom Smith appears to be a good man, but he has secrets of his own, and the others in the grouup seem strangely unaffected by the death of their friend . . . In an unfamiliar city, not knowing who they can trust, Milo and Amory are drawn into the glamorous, dangerous world of nightclubs and bootleggers. But as they draw closer to unraveling the web of lies and half-truths the murdered man has left in his wake, the killer is weaving a web of his own"--.
Keywords: Murder -- Investigation -- Fiction; Mystery fiction